2000
DOI: 10.1061/(asce)0733-9372(2000)126:12(1076)
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH and VFA on Hydrolysis of Organic Solid Waste

Abstract: The anaerobic hydrolysis rate of organic solid waste was studied at fixed volatile fatty acid (VFA) concentrations ranging from 3 to 30 g COD/L and fixed pH values between 5 and 7. For separate control of both VFA and pH, a special completely mixed reactor was designed. In this way, it was possible to distinguish between the inhibitory effects of pH, total VFA, and undissociated VFA on anaerobic hydrolysis. It was shown that hydrolysis of the organic solid waste followed first-order kinetics. Using a statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
90
1
4

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(106 citation statements)
references
References 15 publications
(14 reference statements)
9
90
1
4
Order By: Relevance
“…Many factors, including substrate concentration, hydraulic retention time (HRT), temperature, pH, and process configuration, affect the performance of the acidogenesis phase (Veeken et al 2000;Jeong et al 2010). In conventional complete mixed digesters, HRT approaches the solid retention time (SRT).…”
Section: Effects On Acetogenesis Stagementioning
confidence: 99%
“…Many factors, including substrate concentration, hydraulic retention time (HRT), temperature, pH, and process configuration, affect the performance of the acidogenesis phase (Veeken et al 2000;Jeong et al 2010). In conventional complete mixed digesters, HRT approaches the solid retention time (SRT).…”
Section: Effects On Acetogenesis Stagementioning
confidence: 99%
“…Anaerobic digestion begins with bacteria that hydrolyze complex organic polymers, such as carbohydrates, proteins, lipids and fats, into simple monomeric carbohydrates, amino acids, sugars and long chain fatty acids (LCFA) by extra cellular enzymes. Dry anaerobic digestion generally exhibited a poor startup performance as hydrolysis is a rate-limiting step (Ahn and Smith, 2008;Veeken and Hamelers, 1999;Veeken et al, 2000). The monomeric compounds are then converted by fermentative anaerobic bacteria into a mixture of VFAs and other minor products such as alcohol, carbon dioxide and hydrogen.…”
Section: Basics Of Anaerobic Digestion Processmentioning
confidence: 99%
“…Perhaps the retention time was too short. The role of pH has been discussed by other researchers (Zoetemeyer et al, 1982;Veeken et al, 2000), while Moosa et al (2006) demonstrated that inhibition of biological sulphate reduction is chiefly …”
mentioning
confidence: 98%